Tolerogenic dendritic cells in radiation-induced lung injury - Liu, Benbo; Wang, Yilong; Han, Gencheng; Zhu, Maoxiang (Frontiers in Immunology, 2024)
Radiation-induced lung injury is a common complication associated with radiotherapy. It is characterized by early-stage radiation pneumonia and subsequent radiation pulmonary fibrosis. However, there is currently a lack of effective therapeutic strategies for radiation-induced lung injury. Recent studies have shown that tolerogenic dendritic cells interact with regulatory T cells and/or regulatory B cells to stimulate the production of immunosuppressive molecules, control inflammation, and prevent overimmunity. This highlights a potential new therapeutic activity of tolerogenic dendritic cells in managing radiation-induced lung injury. In this review, we aim to provide a comprehensive overview of tolerogenic dendritic cells in the context of radiation-induced lung injury, which will be valuable for researchers in this field.